Integrated Marketing Communication Tools: Traditional vs. Modern - Oancea, Olimpia; Dutu, Amalia; Diaconu, Mihaela; Brinzea, Mihaela (Journal of Emerging Trends in Marketing and Management, 2016)
This paper proposes to provide a conceptual framework regarding integrated marketing communication tools modern versus traditional. The results of research performed offer the answer at the question: "Are the communication tools modern completely different from those traditional or the principles are the same and differ only new media platforms?". The simplest answer to this question is that probably not really matter as they are called, traditional communication tools or modern communication tools, it is very important how they can create value and efficiency in a world where predominates communications technology. The main conclusions of this study show the fact that in a global market characterized by a high dynamism and strong competition, the challenge for most companies is to identify the most effective tools through which to communicate with actual and potential customers. If initially, the concept of integrated marketing communication took into account the needs and the interests of customers, based on the premise that the integration of its components represents a value both for the customers and for the companies, today it is a certainty that the market is headed and influenced by the customers. Any integrated marketing communication plan should start with a careful analysis of the company's image, the buying behavior of the consumers and communication opportunities. The next important step consist in identification and using the tools of integrated marketing communication considered to be consistent and effective in communication activities of a company.